2016
DOI: 10.1186/s40679-016-0027-9
|View full text |Cite
|
Sign up to set email alerts
|

Detecting structural variances of Co3O4 catalysts by controlling beam-induced sample alterations in the vacuum of a transmission electron microscope

Abstract: This article summarizes core aspects of beam-sample interactions in research that aims at exploiting the ability to detect single atoms at atomic resolution by mid-voltage transmission electron microscopy. Investigating the atomic structure of catalytic Co3O4 nanocrystals underscores how indispensable it is to rigorously control electron dose rates and total doses to understand native material properties on this scale. We apply in-line holography with variable dose rates to achieve this goal. Genuine object st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
0
21
1
Order By: Relevance
“…It was concluded that the image contrast is independent of the electron dose-rate and that strong electron beam-induced atom displacements from their equilibrium positions are absent that would significantly exceed isotropic Debye-Waller factors B = 8 π /3 < u 2 > at room temperature [1] . These findings stand in marked opposition to our recent reports that the electron dose-rate indeed has a marked influence on the HRTEM image contrast [2][3][4][5] . We welcome the opportunity to address the underlying facts and assumptions and find it appropriate to address this apparent discrepancy by demonstrating that the findings in [1] are in fact contained in the results of [2][3][4][5] , which apply to HRTEM images and to imaging in a Scanning Transmission Electron Microscopy (STEM).…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…It was concluded that the image contrast is independent of the electron dose-rate and that strong electron beam-induced atom displacements from their equilibrium positions are absent that would significantly exceed isotropic Debye-Waller factors B = 8 π /3 < u 2 > at room temperature [1] . These findings stand in marked opposition to our recent reports that the electron dose-rate indeed has a marked influence on the HRTEM image contrast [2][3][4][5] . We welcome the opportunity to address the underlying facts and assumptions and find it appropriate to address this apparent discrepancy by demonstrating that the findings in [1] are in fact contained in the results of [2][3][4][5] , which apply to HRTEM images and to imaging in a Scanning Transmission Electron Microscopy (STEM).…”
contrasting
confidence: 99%
“…We expanded the common acquisition practice of single images at a later point of time to include dose-rates as low as 1 e/ Å 2 s, an illuminated sample area that can be more than 100 times smaller than reported in Ref. [1] but remains free of fringes from the presence of apertures, the ability to dramatically alter beam currents by 4-5 orders of magnitude in a fraction of a second without an introduction of uncontrolled lens aberrations, and the ability to correct for residual lens aberrations < 0.5 Å after the acquisition of low-dose-rate image series [2][3][4][5]11] . In fact, our reconstructed electron exit wave functions or in-line holograms exhibit an unmatched sub-Å ngstrom resolution and superior signal-to-noise ratios (SNRs) even if low-doserates < 10 e/ Å 2 s are employed that are much too small to capture interpretable information in single high resolution images because of their poor SNRs.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…A systematic variation of the electron illumination demonstrates that low dose-rates are needed for alleviating beam-induced alterations in the oxide catalysts. Correspondingly, the HRTEM image signal reaches levels at the detection limit but can beneficially be recovered using low dose-rates in conjunction with in-line holography in order to maintain atomic-resolution and -sensitivity of the oxide surface structures (Figure 1) [2][3][4][5][6]. Second, we employ this concept of dose-fractionating electron detection to uncover redox properties of vanadium oxide supported on anatase titanium dioxide nanoparticles (VOx/TiO2) (Figure 2) [6].…”
mentioning
confidence: 99%